*Amor a sombra y sol, de Manuel Cofiño - Henao Salazar, José Ignacio; Castañeda Naranjo, Luz Stella (Íkala, Revista de Lenguaje y Cultura, 2003)
The article presents a brief biography of Manuel Cofiño, which includes an interview with his wife, and an analysis of his novel Love in the Shade and Sun. This work is very important in Cuban literature in the second half of the 20th century. The novel is relevant not only for its literary quality, but also because the relation between the work and the socioeconomic, political and cultural context of Cuba's recent history. Received 30-05-03 / Accepted: 28-06-03. How to reference this article: Henao Salazar, J. I. & Castañeda Naranjo, L. S. (2003). Amor a sombra y sol, de Manuel Cofiño. Íkala. 8(1), pp. 17 – 36